Microelectrodes and radiofrequency for transoral horizontal supraglottic laryngectomy in T3 tumors. Issue 1 (17th October 2022) - Basterra, Jorge; Oishi, Natsuki; Alba, José Ramón; Zapater, Enrique
Abstract: The aim of this manuscript is to show the surgical technique for horizontal supraglottic laryngectomy in T3 carcinomas by a transoral approach using microelectrodes and radiofrequency. From 2009 to 2020, 11 selected cases of T3 laryngeal supraglottic carcinomas invading the pre‐epiglottic space, with preserved vocal cords mobility underwent surgery. The technique is described step by step. Average time duration of the larynx surgery was 95 min. Nine percent of the patients presented a profuse hemorrhage 7 days postoperative; in 73% of patients the nasogastric feeding tube was withdrew 10 days after surgery. We emphasize a remarkable short surgical time and high hemostatic effectiveness. The ME tips allow to perform cuts at angles and contribute with a sense of touch. The low cost of the equipment and its easy handling and maintenance is a remarkable advantage over other technologies for transoral surgery. Abstract : This article supplements the Operative Techniques video presentation, which can be viewed online on Head & Neck's home page at http://onlinelibrary.wiley.com/journal/10.1002/(ISSN)1097‐0347